Efek Suhu Simpan dan Pelapis terhadap Perubahan Kualitas Buah Pisang Cavendish - Bambang S. Purwoko; K. Suryana (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
The objective of the experiment was to determine the effect of coating materials and storage temperatures in inhibiting the ripening process of banana fruits. The experiment consisted of two factors namely storage temperatures (ambient and cool) and coating materials (control, Carnauba wax, bee wax, and Sempefresh). One experimental unit consisted of two fingers of banana. The experiment was replicated three times. Observation was conducted on the following variables: peel color development, weight loss, fruit softening, ratio of flesh and peel weight, sugar content, and titratable acidity. Result of the experiment showed that carnauba wax 6 % inhibited weight loss, fruit softening, and the increase of flesh and peel weight ratio. Bee wax inhibited fruit softening, peel color development and sugar content. Fruit treated with carnauba wax 6 % could be stored at cool temperature for 25.9 days, 10.5 days longer than untreated fruit stored at ambient temperature. Among the three coating materials, Sempefresh had the lowest effectiveness in inhibiting bananaf ruit ripening process.   Key words: Coating, Ripening, Banana, Shelf life